2023
DOI: 10.1002/nop2.1757
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the fully online flipped classroom for nursing undergraduates during the COVID‐19: Historical control study

Abstract: The highly infectious coronavirus disease-2019 (COVID-19) has become a public health event affecting the world. For nursing students, the pandemic has not only affected students' normal in-class learning and clinical placements but also has had a significant impact on students' emotions and well-being (Rasmussen et al., 2022). Some studies indicated that nursing students experienced uncertainty and anxiety during the pandemic (Hamaideh et al., 2022;Roldán-Merino et al., 2022).The government adopted a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Prior research has demonstrated that the conventional FC model—where students learn basic concepts online before class and engage in face-to-face activities during class—typically outperforms traditional teaching methods in enhancing student performance and engagement [ 5 7 ]. However, during the pandemic, several studies reported that students in online flipped classrooms did not achieve superior learning outcomes compared to those in traditional teaching settings, and some students expressed lower satisfaction with instructor motivation and feedback [ 8 12 ]. These findings underscore the need for enhanced interaction and communication in online learning environments.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has demonstrated that the conventional FC model—where students learn basic concepts online before class and engage in face-to-face activities during class—typically outperforms traditional teaching methods in enhancing student performance and engagement [ 5 7 ]. However, during the pandemic, several studies reported that students in online flipped classrooms did not achieve superior learning outcomes compared to those in traditional teaching settings, and some students expressed lower satisfaction with instructor motivation and feedback [ 8 12 ]. These findings underscore the need for enhanced interaction and communication in online learning environments.…”
Section: Introductionmentioning
confidence: 99%